The role of insulin resistance in experimental diabetic retinopathy: genetic and molecular aspects - Järgen, Patrick; Dietrich, Axel; Herling, Andreas W.; Hammes, Hans-Peter; Wohlfart, Paulus (PLOS ONE, 2021)
Background Diabetic retinopathy is characterized by defects in the retinal neurovascular unit. The underlying mechanisms of impairment-including reactive intermediates and growth-factor dependent signalling pathways and their possible interplay are incompletely understood. This study aims to assess the relative role of hyperglycemia and hyperinsulinemia alone or in combination on the gene expression patterning in the retina of animal models of diabetes. Material and methods As insulinopenic, hyperglycemic model reflecting type 1 diabetes, male STZ-Wistar rats (60mg/kg BW; i.p. injection at life age week 7) were used. Male obese ZDF rats (fa/fa) were used as type-2 diabetes model characterized by persisting hyperglycemia and transient hyperinsulinemia. Male obese ZF rats (fa/fa) were used reflecting euglycemia and severe insulin resistance. All groups were kept till an age of 20 weeks on respective conditions together with appropriate age-matched controls. Unbiased gene expression analysis was performed per group using Affymetrix gene arrays. Bioinformatics analysis included analysis for clustering and differential gene expression, and pathway and upstream activator analysis. Gene expression differences were confirmed by microfluidic card PCR technology. Results The most complex genetic regulation in the retina was observed in ZDF rats with a strong overlap to STZ-Wistar rats. Surprisingly, systemic insulin resistance alone in ZF rats without concomitant hyperglycemia did not induce any significant change in retinal gene expression pattern. Pathway analysis indicate an overlap between ZDF rats and STZ-treated rats in pathways like complement system activation, acute phase response signalling, and oncostatin-M signalling. Major array gene expression changes could be confirmed by subsequent PCR. An analysis of upstream transcriptional regulators revealed interferon-γ, interleukin-6 and oncostatin-M in STZ and ZDF rats. CONCLUSIONS: Systemic hyperinsulinaemia without hyperglycemia does not result in significant gene expression changes in retina. In contrast, persistent systemic hyperglycemia boosts much stronger expression changes with a limited number of known and new key regulators.
Published: June 2, 2017
Gesehen am 25.06.2018